Post-Traumatic Stress, Depression, and Quality of Life in Women with Peripartum Cardiomyopathy. Issue 3 (May 2020) - Donnenwirth, Jo Ann; Hess, Rosanna; Ross, Ratchneewan
Abstract: Purpose: Peripartum cardiomyopathy, a traumatic life-threatening type of heart failure, occurs in the last trimester of pregnancy or shortly after childbirth. Little is known about psychological or emotional conditions women experience with peripartum cardiomyopathy. The purpose of this study was to examine relationships among post-traumatic stress, depression, and quality of life in women with peripartum cardiomyopathy. Design and Methods: This cross-sectional, correlational survey study included 28 participants recruited via public notice on Facebook. Participants completed the Horowitz Impact of Events Scale, the Center for Epidemiology Scale–Depression 20, and the Ferrans & Powers Quality of Life Index © –Cardiac Version-IV. Results: Post-traumatic stress correlated significantly and positively with depression ( r = .809, p < .001). Post-traumatic stress and depression correlated significantly and inversely with quality of life ( r = -.455, p = .015), ( r = -.544, p = .003), respectively. All participants measured positive for depression. Participants with lower education scored higher on post-traumatic stress and depression, whereas those unemployed or disabled registered a lower quality of life. Clinical Implications: Nurses, midwives, and physicians caring for women with cardiomyopathies must be vigilant for evidence of post-traumatic stress, depression, and poor quality of life. Targeted antenatal and postnatal support could be vital to emotional and psychological recovery. Abstract : Peripartum cardiomyopathy is a rare and serious cardiac condition of pregnancy. Relationships among post-traumatic stress, depression, and quality of life were evaluated in women living with peripartum cardiomyopathy. Post-traumatic stress correlated significantly and positively with depression, and post-traumatic stress. Depression correlated significantly and inversely with quality of life. All participants measured positive for depression. Nurses should ensure that women with peripartum cardiomyopathy are followed closely for depression and post-traumatic stress.